Large-Scale Whole Genome Sequence Analysis of 22,000 Subjects Provides no Evidence of IFMR1/I Premutation Allele Involvement in Autism Spectrum Disorder - Chubick, Alex; Wang, Evan; Au, Cora; Grody, Wayne W; Ophoff, Roel A (Genes, 2023)
Expansion of a CGG repeat in the Fragile X Messenger Ribonucleoprotein 1 (FMR1) gene on the X chromosome is the cause of Fragile X Syndrome (FXS). The repeat length of unaffected individuals varies between 5–40 repeats, whereas >200 repeats are observed in cases of FXS. The intermediate range between 55–200 repeats is considered the premutation range and is observed in roughly 1:300 females and 1:900 males in the general population. With the availability of large-scale whole genome sequence (WGS) data and the development of computational tools to detect repeat expansions, we systematically examined the role of FMR1 premutation alleles in autism spectrum disorder (ASD) susceptibility, assess the prevalence, and consider the allelic stability between parents and offspring. We analyzed the WGS data of 22,053 subjects, including 32 FXS positive controls, 1359 population controls, and 5467 ASD families. We observed no FMR1 full mutation range repeats among the ASD parent-offspring families but identified 180 family members with premutation range alleles, which represents a higher prevalence compared to the independent WGS control sample and previous reports in the literature. A sex-specific analysis between probands and unaffected siblings did not reveal a significant increase in the burden of premutation alleles in either males or females with ASD. PCR validation, however, suggests an overestimation of the frequency of FMR1 premutation range alleles through computational analysis of WGS data. Overall, we show the utility of large-scale repeat expansion screening in WGS data and conclude that there is no apparent evidence of FMR1 premutation alleles contributing to ASD susceptibility.